Illegal Entrepreneurship: Revisiting the Competition of Part 1 of Article 14.1 of the Administrative Offenses Codeof the Russian Federation and Article 171 of the Criminal Codeof the Russian Federation - A. V. Popov (Сибирское юридическое обозрение, 2019)
Article 171 of the Criminal Code of the Russian Federation and Article 14.1 of the Code of Administrative Offenses of the Russian Federation establish public legal responsibility for conducting business activities without state registration as an individual entrepreneur or legal entity. Thus, the criminal legislation and the legislation on administrative responsibility provide for the adjoining compositions of unlawful acts, which have common features.The article analyzes competing compositions for all elements that form their structure. The Author concludes that the main feature that makes it possible to differentiate criminal and administrative responsibility for the act in question is the degree of its public danger, which is determined by the size of the income received or the harm caused.